How wind energy is contributing to the achievement of Brazilian commitments to the Paris Agreement (Sustainability in Debate, 2022)
The Paris Agreement was signed to reduce greenhouse gas emissions, and Brazil is committed to increasing renewable energy participation in the electrical matrix. This study aims to evaluate how wind energy fulfils the goals determined in the agreement. Through a systematic literature review, 10 relevant studies were identified and together with the analysis of data available in the National Energy Balance report from the Energy Research Company. Comparing the data obtained in the period with the established targets was possible. The success of policies for the sector in reaching the goals above was also evaluated. The results show that wind energy is the renewable source that most benefited from tax incentives and, thus, contributed to the expansion of the share of renewable energy in the Brazilian electrical matrix.